PENGARUH PROPORSI SEPEDA MOTOR TERHADAP KECEPATAN ARUS LALU LINTAS - Erwin Kusnandar (Direktorat Bina Teknik Jalan dan Jembatan, 2010)
Road transport system that has not been effective, resulting in some people prefer a type of mode for transport was motorcycle, the motorcycle is viewed as having advantages in terms of mobility, accesibilitas, and economically, so that the proportion of motorcycles on the road now reaches 6554. Changes in road transportation system due to the high number of users of motorcycles and behavior has. If not treated, trasnsportation system of roads and accidents will be worse. In this paper, we want to give the effect of the number of motorcycles on the road to the speed of vehicles that can be developed by the driver, and also model the relationship as one of alternative answers in determining the proportion of motorcycles on the streets. Relationship variables that are intended, obtained fiom traffic counting amount of each type of vehicle andits speed in each range of time-per-five-minutes, the data is grouped in intervals poroporsi number of motorcycles thatis, condition 1 : 1046 up to 3550, condition 2 : 3540 s/d 7546, and 3 conditions: a merger. Regression analysis method showed there was a positive and significant correlation coefficients with the indicator for the condition I of'0.67, the condition 2 of 0.59, and 0.66 for condition 3. It means that the number of motorcycle affect traffic flow velocity fluctuations. Keyword : in effective transportation, proportionof motorcycles, motorcycle behavior, speed, traffic Slows, Heterogenous traffic